Who says elephants can't dance? : inside IBM's historic turnaround - Gerstner, Louis V. (New York, NY : HarperBusiness, 2002)
In the history of modern business, many companies have gone from being industry leaders to the verge of extinction. Through the heroic efforts of a new management team, some of those companies have even succeeded in resuscitating themselves and living on in the shadow of their former stature. But only one company has been at the pinnacle of an industry, fallen to near collapse, and then, beyond anyone's expectations, returned to set the agenda. That company is IBM. Who says elephants can't dance? tells the story of IBM's competitive and cultural transformation. In his own words, Gerstner offers a blow-by-blow account of his arrival at the company and his campaign to rebuild the leadership team and give the workforce a renewed sense of purpose. In the process, Gerstner defined a strategy for the computing giant and remade the ossified culture bred by the company's own success. The first-hand story of an extraordinary turnaround, a unique case study in managing a crisis, and a thoughtful reflection on the computer industry and the principles of leadership, Who says elephants can't dance? sums up Lou Gerstner's historic business achievement. Taking readers deep into the world of IBM's CEO, Gerstner recounts the high-level meetings and explains the pressure-filled, no-turning-back decisions that had to be made. He also offers his hard-won conclusions about the essence of what makes a great company run.
Includes index.
Keywords: International Business Machines Corporation -- Management; International Business Machines Corporation -- History; Computer industry -- United States -- History; Electronic office machine industry -- United States -- History; Corporate turnarounds -- United States -- Case studies